What is ethnographic about digital ethnography? A sociological perspective - Forberg, Peter; Schilt, Kristen (Frontiers in Sociology, 2023)
When COVID-19 health guidelines vastly restricted or shut down in-person ethnographic research in 2020, many researchers pivoted to forms of online qualitative research using platforms such as WeChat, Twitter, and Discord. This growing body of qualitative internet research in sociology is often encapsulated under the umbrella term “digital ethnography.” But the question of what makes digital qualitative research ethnographic remains open. In this article, we posit that digital ethnographic research necessitates a negotiation of the ethnographer's self-presentation and co-presence within the field that other forms of qualitative research, such as content or discourse analysis, do not require to satisfy their epistemological stance. To make our case, we provide a brief overview of digital research in sociology and related disciplines. Then, we draw upon our experiences conducting ethnographies in digital communities and in-person communities (what we call here, “analog ethnography”) to explore how decisions about self-presentation and co-presence facilitate or block the generation of meaningful ethnographic data. We think through pertinent questions such as: Does the lower barrier for anonymity online justify disguised research? Does anonymity generate thicker data? How should digital ethnographers participate in research environments? What are the possible repercussions of digital participation? We argue that digital and analog ethnographies share a common epistemology that is distinct from non-participatory forms of qualitative digital research—namely the need for the researcher to relationally gather data from the field site over an extended period of time.